Impact of COVID-19 on Public Transport Ridership in Srinagar City (International Journal of Innovative Research in Engineering & Management, 2023)
This paper briefly summarizes the  evaluation of the effects brought on by the devastating  COVID-19 pandemic on public transport ridership. The  transportation industry has been significantly impacted by  COVID-19, thus this study identifies, analyses, and offers  some useful improvement approaches to prevent the  challenges that are currently occurring and being confronted,  notably by stakeholders and the public. A questionnaire form  was created, and with the aid of web based survey, a sample  size of 180 survey forms was completed while taking into  account D Morgan's Table. Data and replies were gathered  using the main data source. This is the initial study on the  effects of COVID-19 on transportation in Srinagar (Jammu  and Kashmir, India), and it is anticipated that it will be  crucial in reducing the adverse effects of a pandemic on  Srinagar's transportation industry. In addition, the study  emphasizes a number of significant elements that are very  likely to affect travelers’ choices in the post-pandemic  period. Factors such as respondents' regular modes of  transportation during the pre-COVID-19 period, their  frequency of public transportation use in that time period,  their anticipated change in trip frequency and virtual  activities during the "new normal" situation, their perception  of risk, and their confidence in preventive measures all had  an impact on the anticipated change in frequency of travel by  public transportation during that time period.
Keywords: COVID-19; Public; Transportation; Srinagar; India